ANALISIS PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN PENGADILAN TINDAK PIDANA KORUPSI PADA TINGKATAN PENGADILAN YANG BERBEDA (STUDI PUTUSAN PERKARA TIPIKOR DANA DESA TUGUIS KABUPATEN HALMAHERA UTARA TAHUN 2022) - Jitro Sulani; Faissal Malik; Anshar Anshar (Khairun Law Journal, 2024)
This article discusses legal considerations in court decisions on corruption of village funds at two different court levels based on Decision Number 5/Pid.Sus-TPK/2022/PN Tte at the first level and Decision Number 6/Pid.Sus-TPK/2022/PT Tte at the appeal level. The legal issue lies in the difference in judges' legal considerations related to the application of Article 2 paragraph (1) and Article 3 of the Corruption Eradication Law. This research uses normative legal research with secondary data sourced from primary and secondary legal materials. In the data collection process, data collection techniques are used by means of literature studies which are then processed and analyzed qualitatively. The panel of judges who examined and tried the case of corruption of village funds based on the Corruption Court Decision at the North Maluku High Court Number 6/Pid.Sus-TPK/2022/PT Tte after examining based on legal facts had a different view from the panel of judges at the previous level. The judge at the high court level after examining the case file and based on the legal facts in the trial at the first level concluded that what was proven was not the primary charge of Article 2 paragraph (1) but the secondary charge of Article 3 with all legal considerations. However, in relation to the punishment imposed by the judge at the higher level, there is no difference with the form of punishment imposed by the judge at the first level. Both the imposition of imprisonment, fines and additional punishment in the form of payment of restitution.